Avaliação de polimorfismos de genes de reparo em pacientes com carcinoma epidermóide de cabeça e pescoço e a relação do prognóstico e radiossensibilidade tumoral - Stur, Elaine (2014)
DNA repair gene polymorphisms have been suggested as putative markers for prognosis and radiosensibility in patients with head and neck squamous cell carcinoma (HNSCC). Therefore, we have aimed to study polymorphisms in repair genes XRCC1 (rs1799782 and rs25487), XRCC3 (rs861539), XPC (rs2228001), ERCC1 (rs11615) and RAD51 (rs1801320), in order to evaluate their influence in the radiotherapy response and prognosis in HNSCC. Genotypes were determined by DNA extracted from perypheral blood of 311 patients with HNSCC, after PCR-RFLP analysis. Polymorphisms XRCC1 Arg399Gln showed that alelle 399Gln increases disease relapse risk in irradiated patients with oral and oropharyngeal tumors (OR=3.35; CI= 1.10-10.13).